Migration and Distribution Characteristics of Proppant at the Corner of Horizontal Fracture Network in Coal Seam - Cheng, Qingying; Li, Haoze; Huang, Bingxiang; Zhao, Xinglong; Sun, Zheng; Jiao, Xuejie; Li, Heng (Frontiers in Earth Science, 2021)
Complex fracture network is composed of many similar structures. The migration law of proppant at each structure is the core and basic content of the migration law of proppant in complex fracture network, and there is little research. In this paper, the Eulerian-Eulerian method (TEM) is used to analyze the migration and distribution characteristics of solid-liquid two phases at the fracture corner according to different corner types of fracture network. The results show that the migration characteristics of proppant in the corner area can be divided into corner anomaly area, buffer area and stability area; The influence of turning angle on proppant migration is mainly concentrated at the corner and in the range of 4 times the fracture width after turning. The probability of sand plugging at the corner of "Y → T" fracture is lower than that of "L → l"; higher than that of "X → +" wing branch fracture, and lower than that of main fracture. At the corner of the fracture network, after the solid flow turns, the proppant will form a high sand area on the side of the impact fracture surface, then rebound back to the fracture, form a sand free area on the other side, and form a high velocity core in the refraction interval. At the corner of "L → l" fracture, there are one high sand area, one non sand area, two low velocity areas and one high velocity area; There are three low velocity areas, two sand free areas and one high sand area at the corner of "Y → T" fracture; At the corner of "X → +" fracture, there is a high sand area, no sand free area, and the flow velocity of the main fracture is much greater than that of the wing branch fracture.